Diversity and Genetic Erosion of Ancient Crops and Wild Relatives of Agricultural Cultivars for Food: Implications for Nature Conservation in Georgia (Caucasus) - Akhalkatsi, Maia; Ekhvaia, Jana; Asanidze, Zezva (IntechOpen, 2012)
None